Model projects as tools for cooperative urban development: The case of Haus der Statistik in Berlin. Issue 1 (1st September 2022) - Gundlach, K; Marlow, F; Peters, N; Wall, R
Abstract: According to the New Leipzig Charter, urban development processes should be 'a matter of all' – the common good, climate protection and environmental justice, to name but a few aspects. Currently, new forms of innovation seeking models emerge within this context of sustainable urban planning practice - for example, real-world field laboratories and model projects. Haus der Statistik in Berlin is one such 'model project for cooperative and common-good-oriented urban development'. It is widely recognized for its demand- and process-driven approach, as well as its project development being based on public-civic partnership. As anthropological and urbanist researchers and practitioners involved in the project, we give a situated account on the socio-political elements of the Haus der Statistik's public-civic partnership and investigate the potentials of this model for a more sustainable urban development. The structure of the paper is threefold: Firstly, we introduce the so-called model project Haus der Statistik and its common-good orientated agenda and relate it to sustainability goals of the New Leipzig Charter. Secondly, we introduce the specific public-civic-framework in regard to its methodological framing within the context of model projects and comparable approaches that focus on collaborative, transdisciplinary and innovative methods, such as real-world field laboratories. Thirdly, we reflect on the elements of the public-civic-partnership framework that have been explored and developed at the 'model project' Haus der Statistik since 2015 and its implications for a more sustainable urban development.